Chapter The life of Mario Tchou in the graphic novel La Macchina Zero. A transnational Sino-Italian scientist - Scibetta, Andrea (Studi e saggi, 2023)
The current contribution aims at describing some key aspects in Rocchi and Demonte's graphic novel La Macchina Zero, published in 2021. This is Rocchi and Demonte's third work narrating stories of Chinese migration to Italy, after Primavere e Autunni (2015) and Chinamen (2017). Differently from the first two graphic novels, La Macchina Zero gives back to collective memory a new glimpse on the history of Chinese in Italy, focusing on the role of Mario Tchou, a brilliant Sino-Italian electronic scientist, and his contribution both to the economic growth of the Olivetti enterprise and to the creation of one of the first new generation computers, ELEA 9003. The first part will highlight on the main events narrated in the graphic novel. After that, some specific considerations about the structure and style, semiotic aspects and communicative functions of La Macchina Zero will also be provided, also in comparison with the previous two works. The third paragraph will specifically focus on Mario Tchou, his life and his crucial contribution, as a transnational scientist, to the ascent of Olivetti worldwide.